2004
DOI: 10.1108/00012530410570390
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating internet usage and ecommerce growth in Greece

Abstract: According to studies and surveys conducted world‐wide, government incentives and current legal frameworks, private initiatives and investments, technology available at a reasonable price, and public acceptance of the internet as an efficient medium for buying goods and services are driving ecommerce growth. Academics, information technology experts and even politicians in Greece are aware of these essential requirements as well. However, although internet access has grown significantly and the digital foundati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…Papastathopoulo and Avlonitis [3] have attempted, firstly, to determine several indexes for different businesses in respect of their policies in using the web space and, secondly, to pinpoint the relationships between the type of use of the world-wide web in general with the demographic characteristics of the top companies of Greece, having, finally, concluded that the type of webuse profiles in those companies could be classified into distinct groups. Zantidis and Nicholas [4] in investigating the types of Internet usage in Greece and its impact on the procurement of e-commerce in that country, consider the advancement of information technology, the development of the required equipment for creating e-commerce websites, and expansion of Internet use as three of the main concerns of Greek government, coming to the conclusion that the governmental incentives, the reduction of the costs of the necessary technologies, and the public acceptance of the Internet as the medium for buying and selling could be regarded as crucial factors for success in e-commerce.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Papastathopoulo and Avlonitis [3] have attempted, firstly, to determine several indexes for different businesses in respect of their policies in using the web space and, secondly, to pinpoint the relationships between the type of use of the world-wide web in general with the demographic characteristics of the top companies of Greece, having, finally, concluded that the type of webuse profiles in those companies could be classified into distinct groups. Zantidis and Nicholas [4] in investigating the types of Internet usage in Greece and its impact on the procurement of e-commerce in that country, consider the advancement of information technology, the development of the required equipment for creating e-commerce websites, and expansion of Internet use as three of the main concerns of Greek government, coming to the conclusion that the governmental incentives, the reduction of the costs of the necessary technologies, and the public acceptance of the Internet as the medium for buying and selling could be regarded as crucial factors for success in e-commerce.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Operations-based competitiveness in E-Commerce requires the development of competencies, those competencies are supportive and there is linkage between competencies in E-Commerce operations and strategy (Sharif kamel, 2002). E-commerce represents opportunities to remain swiftness with the developed world and its evolution is forcing many nations to change their policies for the business and socio-economic development (Dimitrios Xanthidis and David Nicholas, 2004). However it is incomprehensible for any government to develop a huge and vigorous information society except only when the consumers and companies find the value of the digital economy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Apart from limitations by the available technological infrastructure and the government initiatives and incentives to businesses, the behavior of users is one of the most important drivers for this relatively low level of internet usage. Therefore, it is important to perform an in‐depth analysis of current customer preferences and examine the factors that influence customer loyalty intensions, so that struggling companies might design more effective customer retention strategies (Xanthidis and Nicholas, 2004).…”
Section: Introductionmentioning
confidence: 99%